Pericardio-diaphragmatic rupture after blunt trauma: a case report - Xing, Dayi; Xia, Boyu; Yang, Jiandong; Zhao, Yuansheng (Frontiers in Surgery, 2025)
BackgroundPericardio-diaphragmatic rupture with intrapericardial herniation is a rare and potentially life-threatening complication of blunt thoracoabdominal trauma. Its diagnosis is challenging because pericardial involvement is often missed on imaging.Case presentationWe present the case of a 70-year-old man who sustained blunt chest trauma in a motor vehicle collision. On admission, he was hemodynamically stable, and echocardiography demonstrated preserved left ventricular function (ejection fraction 59%) without pericardial effusion. Initial CT demonstrated multiple right rib fractures and pulmonary contusion. Repeat CT at our center revealed bilateral lower lobe atelectasis, small pleural effusions, and a bowel gas shadow anterior to the heart, suggestive of diaphragmatic rupture with intrapericardial herniation. Thoracoscopic exploration excluded right-sided injury; however, laparoscopic inspection identified a large left diaphragmatic tear (10 cm) with bowel and omentum herniating into the pericardial sac in direct contact with the epicardial surface. Due to limited exposure and high tension, the procedure was converted to median sternotomy for safe repair. Postoperative CT confirmed resolution of the hernia. The patient recovered uneventfully and remained asymptomatic at 3-month follow-up.ConclusionsPericardio-diaphragmatic rupture with intrapericardial herniation is rare and often underdiagnosed because of nonspecific clinical features and subtle imaging findings. Median sternotomy should be considered when minimally invasive repair is not feasible, and combined thoracoabdominal evaluation is crucial for diagnosis and management.